Muscle damage and fatigue in the marathon - Del Coso, J.; Salinero, J. J.; Abian-Vicen, J.; Gonzalez-Millan, C.; Garde, S.; Vega, P.; Perez-Gonzalez, B. (New Studies in Athletics, 2012)
Is muscle fatigue in the marathon related to body mass change (dehydration) and/or muscle damage produced by the continuous foot strikes over the 42.2km distance? For this study, adapted from a paper originally published in Applied Physiology Nutrition and Metabolism Journal, amateur runners (114 men and 24 women) were tested before a marathon for leg muscle power output, their body weight was recorded and a urine sample was obtained. Within three minutes of completing the race, run in 28oC and 46% relative humidity, the subjects repeated the leg power test and then their body weight and urine samples were collected again. The authors found that mean body mass reduction was 2.2±1.2%. The body mass change shows high inter-individual variability, but only 7% of the runners studied lost more than 4%. No myoglobin (a protein indicating muscle fibre damage) was detected in the pre-race urine specimens while postrace urinary myoglobin concentration increased to 3.5±9.5 µg/mL (P<0.05). Mean leg muscle power reduction after the race was 16±10%. Muscle power change significantly correlated with post-race urine myoglobin concentration (r=-0.55; P<0.001) but not with body mass change (r=-0.08; P=0.35). The correlation between myoglobinuria and muscle power change suggest that muscle fatigue is associated with muscle tissue breakdown.